Studies on racemic triglycerides as urease enzyme inhibitors (Bangladesh Journal of Pharmacology, 2025)
Amidohydrolase enzymes regulate key pathways, and their dysregulation is linked to infection, immune imbalance, and metabolic dysregulation in cancer. Current inhibitors have issues of cost, environmental persistence, and toxicity. Here, triglyceride-derived inhibitors were investigated as low-cost, synthetically viable, and eco-friendly candidates targeting the metalloenzyme catalytic pocket of urease, a representative member of the amidohydrolase family. A cyclic triglyceride ester series (10a–c) were synthesized and characterized by standard spectroscopic methods. Racemic compound (10a) exhibited potent urease inhibition (IC₅₀ = 14.2 µM), surpassing thiourea (IC₅₀ = 21.6 µM). Molecular docking showed key interactions with CME592 and Arg439 residues in the catalytic pocket. To rank the (R) and (S) enantiomers, a molecular dynamics scoring approach was applied, integrating real-time hydrogen-bonding, Coulombic, and hydrophobic interactions. Both enantiomers showed comparable dynamic scores, validating the racemate’s activity. These findings suggest cyclic triglyceride scaffolds as promising inhibitors for urease and potential candidates for other amidohydrolase enzymes.